Design and Build Financial Information System and Administration of SMK Tunas Harapan West Jakarta using the Extreme Programming Method - Muhammad Rendi; Ratna Yulika Go (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
SMK Tunas Harapan West Jakarta currently manages a substantial student body of 1,050 active students across various vocational programs. However, its financial and administrative management is still conducted manually using conventional tools such as physical ledgers and standalone spreadsheets. This outdated approach frequently causes delays in data retrieval, difficulties in financial report recapitulation, and high risks of human error during payment processing. Furthermore, this condition is exacerbated by a lack of integration between departments, leading to inconsistent information and inefficient monitoring. To address these critical challenges, this study aims to design and develop an integrated, web-based financial and administrative information system utilizing the Extreme Programming (XP) method. The XP methodology was chosen for its adaptability, involving continuous stages of planning, simple design, pair programming coding, testing, and continuous integration. Data collection techniques included observations, structured interviews, and document studies , followed by an in-depth analysis using the PIECES framework. The developed system is built on the Laravel 12 framework, PHP, JavaScript, and MySQL. It offers comprehensive features such as online student registration, automated billing management, payment verification, and digital receipt generation. Based on Black Box Testing, all system modules functioned perfectly as intended. Additionally, User Acceptance Testing (UAT) conducted with 92 respondents yielded a high user satisfaction rate of 86.49%. In conclusion, this system effectively modernizes the school's administrative workflow, improves financial transparency, and is deemed highly suitable for implementation